EFEKTIVITAS PELAKSANAAN PROGRAM BHAKTI TNI MANUNGGAL MEMBANGUN DESA DI KECAMATAN SAMBUTAN TAHUN 2017 - Mustofa mustofa (ADMINISTRASI PUBLIK, 2018)
TNI Bhakti Program is an integrated activity that can be used as a solution the center of the local government budget constraints in the welfare of people in rural areas, the program of TNI Manunggal Village building (TMMD) that was held in the Panaragan village in 2014.Focuses on the opening of how roads program activities that have been planned and surveyed by related parties (uspika) Sambutan District of Center, on the basis of the description of the writer felt draw to research activities of bhakti TMMD in the Makroman village in 2017, whether thesa activities have been effective. For the purpose of this study is to Bhakti TNI Manunggal Village Building (TMMD) in the village.The methode used is the study is qualitative with descriptive research type.The techhnique of collecting data using interviews and documentation, as well as data management techhnique used are editing and interpretation, while the data analist presented by data reduction, display of data and taking conclusions.The result of research in the field showed that in terms of the implementation of Bhakti TNI Manunggal Village Building program (TMMD) in the Makroman village has been running effectively, because it has camplied the indicator of the effectiveness a program with we the theory of indicators Richard M. Steers are indicator of goal achievement, indicator of integration and adaptation. The activities of Bhakti TNI Manunggal Village building has complied the indicator on the theory.